KUALITAS PELAYANAN PEMBUATAN SERTIPIKAT TANAH DI KANTOR AGRARIA DAN TATA RUANG/BADAN PERTANAHAN NASIONAL KOTA MANADO - MONA, DANIEL BLAISE PASCAL; RURU, JOORIE MARHAEN; LONDA, VERY (Sam Ratulangi University, 2017)
Abstract : Service can be defined as providing services (serving) the needs of people or communities who have an interest in theorganization in accordance with the rules and procedures that have been established. When associated with publicadministration, service is the quality of bureaucratic service to the community. Quality of service in general can be seen fromsome of the characteristics that determine the good of a service product that comes from government policy. Based on initialobservations made by researchers at the Agrarian Office and Spatial/Land Agency of Manado City, there are several problemsthat still occur in the process of making land certificate service which some of them complained about by the public. This studyaims to determine the Quality of Land Certificate Preparation Service in the Agrarian Office and Spatial/National Land Agencyof Manado City. The quality of public services can be measured from five dimensions, namely tangible, reliability,responsiveness, assurance, and empathy. The research method used is qualitative, where research is used to research on naturalobject condition, and the researcher is the key instrument. Sources of research data consist of primary data and secondary data.The research informant consisted of officials and employees of service providers as well as a community of service users totalingfifteen persons. Technique of collecting data is done by observation, interview, documentation and triangulation. This researchuses data analysis techniques from Miles and Huberman which consists of three steps, namely data reduction, data presentationand conclusion.Keywords: Service Quality, Making Land Sertificates.